ПЕРЕЊЕТО ПАРИ И ЕКОНОМСКИОТ РАСТ СО ОСВРТ НА РЕПУБЛИКА МАКЕДОНИЈА - Ненад НИКОЛОВСКИ (Bezbednosni Dijalozi, 2011)
The economic growth is a multidimensional component, which consists of numerous of macroeconomic parameters, which are usually measurable and interconnected. Their relationship and interaction should create optimal combination and in the final sense should lead to economic growth. The constituent elements of this multidimensional component are reflected in macroeconomic parameters with positive influence from one side and with negative influence on the other side in order to achieve economic growth. The money laundering leads to a negative correlation with economic growth and produce economic bases oppose to the mechanism of the invisible hand of the market and fair competition. This deviant and criminal phenomenon in society should be measured and consistent to be included into the preparing of the future macroeconomic policies. Only in this way, legally produced capital will be ensured stablity and sustainable economic growth.